2015
DOI: 10.1371/journal.pone.0128085
|View full text |Cite
|
Sign up to set email alerts
|

The Histological Components of the Phoniatrical Body-Cover Model in Minipigs of Different Ages

Abstract: Pigs are models in human phoniatry. However, features of maturation and ageing have not been considered with regard to the so-called body-cover model in this species. Therefore, the glottis of “young” (2–3 months; n = 6) and “old” (4–7 years; n = 6) minipigs was investigated. Their cranial (CraF) and caudal (CauF) vocal folds were histomorphometrically and stratigraphically analysed with emphasis on their amounts of collagen structures and elastic fibres. A dense subepithelial layer (SEL) was a distinct featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In summary, these results show that old sheep exhibit (1) stiffer collagen network due to thicker and shortened fibers; (2) lower tissue viscoelasticity due to reduced HA-level, resulting in reduced water storage and hence in reduced ability to shock absorption due to the constant trauma caused by the vibratory actions of phonation; (3) increased inertance yielding a reduced dynamic range; (4) more random distributed fat inclusion that may to a certain point also explain the reduced systematic behavior in the phonatory experiments; (5) reduced elastin concentration, yielding less changes in vocal fold elongation and hence less overall accurately dynamical measurable differences. These results are consistent with the previously published results in human, rat, and mini-pig aging larynx [ 24 26 ].…”
Section: Resultssupporting
confidence: 94%
“…In summary, these results show that old sheep exhibit (1) stiffer collagen network due to thicker and shortened fibers; (2) lower tissue viscoelasticity due to reduced HA-level, resulting in reduced water storage and hence in reduced ability to shock absorption due to the constant trauma caused by the vibratory actions of phonation; (3) increased inertance yielding a reduced dynamic range; (4) more random distributed fat inclusion that may to a certain point also explain the reduced systematic behavior in the phonatory experiments; (5) reduced elastin concentration, yielding less changes in vocal fold elongation and hence less overall accurately dynamical measurable differences. These results are consistent with the previously published results in human, rat, and mini-pig aging larynx [ 24 26 ].…”
Section: Resultssupporting
confidence: 94%
“…5 ). Because previous studies showed that the quantity of collagen in skin is an important indicator of aging 27 28 29 30 31 , the medial thickness of the collagen in skin was quantitated using the Image-J system. The medial thickness of collagen in skin after the 3-month experimental period was 327.8 ± 13.4 μm in the DJ526 group, 203.3 ± 7.5 μm in the DJ group, 204.4 ± 10.2 μm in the RS group, and 177.8 ± 7.0 μm in the control group ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). It has been well known that a thick collagen layer in the body indicates youth in mammals, and the collagen layer becomes thinner as it ages 27 28 29 30 31 . Therefore, the healthy thickness of collagen as well as up-regulation of anti-aging related pathways in the DJ526 treated group can explain why the DJ526-treated mice were vastly superior in physical strength than the RS or DJ treated group.…”
Section: Discussionmentioning
confidence: 99%